Notes from the Orchid Station, Tipi, Arunachal Pradesh - A Note on the Cultivation of Orchids - Kataki, S. K. (Indian Forester, 1978)
This paper presents a short account on the cultivation of orchids at the Orchid Station, Tipi in Arunachal Pradesh.